PENEGAKAN HUKUM PIDANA DALAM PELAKSANAAN PEMILIHAN GUBERNUR DI JAWA TIMUR - ISNAWATI , MURIDAH (2011)
Direct regional head elections (elections) is one of the objectives of decentralization in the framework of regional autonomy. Election of regional head and deputy head of the regulated area in one part of Law Number 32 Year 2004 on Regional Government, namely in Section Eight of Article 56 through Article 119. Research conducted by the author is research on the Implementation of Criminal Law Enforcement In East Java gubernatorial election as a reflection of the implementation of democratic elections. Implementation of the East Java gubernatorial election held three rounds of course not independent of the number of violations that occurred well-pelanggara administrative violation or criminal offense. This study will examine specifically about the violations that are criminal who was found in East Java Pilgub pelaksannan and how law enforcement efforts. The research method used in this research is a qualitative method with case studies. While the analysis of the data used in this research is an interactive analysis. Cases are taken and analyzed in this study are the violations that occurred primarily at the commencement of criminal offenses in the East Java gubernatorial election in 2008. The results of this study indicate that there are still many violations that occurred during the execution of both East Java pilgub administrative violation or criminal offense, so pilgub exercised until three rounds. Of the various phenomena of criminal violations that occurred during the execution pilgub in some areas in East Java, which has authors describe both before, during and after implementation of pilgub place, quite an impact on the democratic process that has taken place in East Java at the time. Until pilgub must be held for 3 rounds, although acknowledged that many violations are processed by the rules regarding pilgub, especially the rules stipulated in Law No. 32 of 2004 but the settlement procedures there are still many shortcomings, especially regarding the Code of Criminal Procedure was good in the process Investigation, Prosecution and Investigation in the trial court.